2011
DOI: 10.3382/ps.2010-01264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xylanase and citric acid on the performance, nutrient retention, and characteristics of gastrointestinal tract of broilers fed low-phosphorus wheat-based diets

Abstract: An experiment was conducted to study the effects of xylanase and citric acid on the performance, nutrient retention, jejunal viscosity, and size and pH of the gastrointestinal tract of broilers fed a low-P wheat-based diet. The experiment was conducted as a 2 × 3 factorial arrangement with 2 levels of xylanase (0 and 200 mg/kg) and 3 levels of citric acid (0, 20, and 40 g/kg). Each of the 6 dietary treatments was fed to 4 replicate pens (17 birds/pen) from 0 to 24 d of age. Chromium oxide (3 g/kg) was added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 38 publications
4
32
0
2
Order By: Relevance
“…Brenes et al (2003) reported that addition of phytase and citric acid to LAPD (0.25% available P) increased retention of P in broiler chickens. Esmaeilipour et al (2011) also observed higher retention of P in broilers fed with LAPD (0.27% available P) supplemented with citric acid. Sodium citrate has not similar effect on pH as citric acid (Skoog et al 2004) but it has been proposed that sodium citrate is more powerful chelator of Ca than phytate.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Brenes et al (2003) reported that addition of phytase and citric acid to LAPD (0.25% available P) increased retention of P in broiler chickens. Esmaeilipour et al (2011) also observed higher retention of P in broilers fed with LAPD (0.27% available P) supplemented with citric acid. Sodium citrate has not similar effect on pH as citric acid (Skoog et al 2004) but it has been proposed that sodium citrate is more powerful chelator of Ca than phytate.…”
Section: Discussionmentioning
confidence: 64%
“…Esmaeilipour et al (2011) observed that citric acid supplementation to wheat-soybean meal-based diet (low in P) increases the P retention in broilers. The mechanism of increased phytate-P utilization by citric acid is not well known yet in chicks (Rafacz-Livingston et al 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Other researchers reported that butyric acid did not depress the FI, whereas the FI was depressed by propionate acid (Leeson et al, 2005). High levels of OAs added to the diets of laying hens also reduced the FI (Dibner and Buttin 2002;Esmaeilipour et al, 2011). They may exert this effect on laying hens by changing the palatability of the food.…”
Section: Resultsmentioning
confidence: 98%
“…Previous experiments have reported that dietary organic acids can increase phosphorus utilization in corn-soybean meal diets fed to broiler chickens (Boling et al ., 2000;Esmaeilipour et al ., 2011). Phosphorus utilization may be increased due to the chelating properties of organic acids with calcium, which can result in increased phytate-phosphorus solubility, increasing their ability to be hydrolyzed (Centeno et al ., 2007).…”
Section: Other Possible Effectsmentioning
confidence: 99%
“…It is postulated that excessive amounts of dietary citric acid inclusion may compromise performance because two experiments using 60 g/kg citric acid in diets reported significant decreases in body weight gain. (Patten and Waldroup, 1988;Alçiçek et al, 2004;Leeson et al, 2005;Gunal et al, 2006;Hernández et al, 2006;García et al, 2007;Paul et al, 2007;Biggs and Parsons, 2008;Pirgozliev et al, 2008;Samanta et al, 2008;Al-Kassi and Mohssen, 2009;Ao et al, 2009;Bozkurt et al, 2009;Chowdhury et al, 2009;Kim et al, 2009;Mahdavi and Torki 2009;Panda et al, 2009a,b;Haque et al, 2010;Nourmohammadi et al, 2010;Smulikowska et al, 2010;Esmaeilipour et al, 2011;SalgadoTránsito et al, 2011;Aghazadeh and Tahayazdi, 2012;Nourmohammadi et al, 2012;Świątkiewicz and Arczewska-Wlosek, 2012). 2 Detailed information for each organic acid was provided in the Tables 5 through 9.…”
Section: Citric Acidmentioning
confidence: 99%